2012
DOI: 10.2308/iace-10220
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis of the Pedagogical Approach Employed in an Introductory Course to IFRS

Abstract: This paper, through case analysis employing analytical autoethnography, investigates the pedagogical approach employed in an introductory course to IFRS. This course is part of a professional accounting education program in South Africa. The analysis reflected the teacher-centered orientation of the pedagogy employed, despite warnings in the literature that such an approach may be inappropriate in educating future accounting professionals. The adopted approach has, however, contributed to the success of alumni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 49 publications
0
30
0
6
Order By: Relevance
“…A contabilidade financeira e a gerencial se relacionam no processo contábil e decisório. Como forma de desenvolvimento, há uma necessidade de melhor preparação do ensino na área financeira, assim como na área gerencial, tendo em vista a relação estreita e vinculante entre as duas bases contábeis (CAMPBELL; HELLELOID, 2011;COETZEE;SCHMULIAN, 2012). Necessidades mais imediatas são percebidas em função do custo dos produtos, impactos na análise de investimentos em função da vida útil dos ativos e do aumento ou redução da depreciação.…”
Section: Processo De Formação Acadêmica: a Preparação Do Profissionalunclassified
“…A contabilidade financeira e a gerencial se relacionam no processo contábil e decisório. Como forma de desenvolvimento, há uma necessidade de melhor preparação do ensino na área financeira, assim como na área gerencial, tendo em vista a relação estreita e vinculante entre as duas bases contábeis (CAMPBELL; HELLELOID, 2011;COETZEE;SCHMULIAN, 2012). Necessidades mais imediatas são percebidas em função do custo dos produtos, impactos na análise de investimentos em função da vida útil dos ativos e do aumento ou redução da depreciação.…”
Section: Processo De Formação Acadêmica: a Preparação Do Profissionalunclassified
“…Springer and Borthick (2007), Coetzee and Schmulian, (2012) and Jarvis et al, (2014) all noted that the lecture model is primarily teacher-centric, and negative perceptions of accounting were common among accounting students (Mladenovic, 2000).…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…The lecture model is still predominately the pedagogy for teaching undergraduate accounting students today (Coetzee & Schmulian, 2012;Jarvis et al, 2014). As early as the 1970's researchers demonstrated that teaching pedagogies that are teacher-centric (lecture model) will only produce surface or fragmented understanding for students (Marton & Säljö, 1976).…”
Section: The Lecture Modelmentioning
confidence: 99%
See 2 more Smart Citations